Design and innovation to enhance SMes’ new product development / Nur Haizal Mat Yaakob@Ariffin - Mat Yaakob@Ariffin, Nur Haizal (Institute of Graduate Studies, UiTM, 2018)
Design and innovation play a very significant role in producing innovative and high added value of products through new product development (NPD) process thus can enhance the SMEs’ performance. However, the numbers of SMEs manufacturing involved in developing product by utilizing design and innovation is not at a good level. In order to understand how design and innovation has been practiced in the SMEs in developing new product, this research combined quantitative and qualitative data collection methods including a literature review, questionnaire survey and interview. Interviews include open ended and semi-structured interviews with staff who directly involved in the process of NPD, questionnaire surveys helped to provide background and validate findings from the secondary sources. Both data for quantitative and qualitative were collected through industrial designers, marketers and decision makers. The study has focused on SMEs in furniture, consumer durable product and automotive industries. The interviews focused on six issues (‘Parties involve’, ‘Implementation’, ‘Management’, ‘Performance achievement’, and ‘Quality’. An overall finding shows that even though most SMEs know the importance of design and innovation as their sources of competitive advantages, however they are not fully engaged with the activity as they feel it would increase their operation costs. Additionally, they are more focused on generating profits in a short time rather than doing something risky…